Are egg production and respiration of the marine pelagic copepod Acartia steueri influenced by crowding?. (4th July 2020) - Takayama, Yoshiki; Hirahara, Minamo; Liu, Xin; Ban, Syuhei; Toda, Tatsuki
Abstract: The understanding of the biological responses of copepods under crowding conditions contributes to establish their stable cultures at high densities for aquaculture industry, which are preferred live feeds for fish larvae. The present study investigated survivorship, fecundity, hatching success and respiration rate, of Acartia steueri raised under five densities, from 100 to 2, 000 ind. L −1, to clarify the biological responses of the copepod under dense culture. There were no significant differences in survival, fecundity and hatching success among all density conditions, whereas the respiration rate at 2, 000 ind. L −1 decreased by 80% as compared with a condition at 100 ind. L −1 . The female copepods raised under a copepod density of >500 ind. L −1 probably invested a larger proportion of energy in reproduction in relation to total assimilated energy as compared with females under lower copepod densities. This change of energy allocation may allow A. steueri under high densities to maintain high fecundity. Acartia steueri might be a promising species for dense culture because its mortality and fecundity were independent of the effect of crowding, and the density‐dependent reduction in the metabolic rate might increase reproductive investment to maintain a constant rate of reproduction even under high densities.